Anticipated Consumer Guilt: An Investigation into its Antecedents and Consequences for Fair-Trade Consumption. (December 2017) - Lindenmeier, Jörg; Lwin, Michael; Andersch, Henrike; Phau, Ian; Seemann, Ann-Kathrin
This study considers fair-trade as a collaborative strategy of dealing with the wicked problem of apparel sweatshops. The study assumes that consumer guilt increases the market share of fair-trade products which can be regarded as a favorable change in the marketing system's output. The paper develops and validates a model of guilt-induced fair-trade buying based on this notion. The model comprises negative affect, ethical judgment, and self-efficacy as antecedents of anticipated consumer guilt. The study's results, based on a sample of American consumers (n = 430) and analyzed in a structural equation model, reveal anticipated guilt as a major driver of fair-trade buying behavior. Furthermore, anticipated consumer guilt mediates the effects of its antecedents on fair-trade buying intention. The paper provides implications for macro-decision making (e.g., guilt-inducing nudges) as well as suggestions for marcromarketing research.